Relationship between different anti-rheumatic drug therapies and complementary and alternative medicine in patients with rheumatoid arthritis: an interview based cross-sectional study - Haya M. Almalag; Aseel M. Almuhareb; Aya A. Alsharafi; Tariq M. Alhawassi; Ahmed A. Alghamdi; Hussain Alarfaj; Mohammed A. Omair; Bedor A. Alomari; Maysoon S. Alblowi; Hanan H. Abouzaid; Abdurhman S. Alarfaj (Saudi Pharmaceutical Journal)
Objectives: The use of complementary and alternative medicine (CAM) by patients with rheumatoid arthritis (RA) is highly prevalent. The relationship of these remedies with disease therapy are not fully studied. We aimed to explore the relationship between different anti-rheumatic drug therapy and CAM use in RA patients. Methods: The study used an interview-based cross-sectional survey in two major referral centres in Riyadh, Saudi Arabia. Patients were adults with confirmed RA that attended rheumatology clinics. Information on the utilization of CAM, RA duration, drug therapy, and laboratory parameters were obtained. Descriptive statistics as well as adjusted odds ratio using bivariate logistic regression were used to explore the different factors related to CAM use, including drug therapy. Results: A total of 438 adult patients with RA were included. The mean (±SD) age of the patients was 49 (±15.0) years. The majority were women 393 (89.7%). Two hundred and ninety-two patients (66.7%) had used CAM. The CAM users who had a longer disease duration (AOR 1.041 [95% CI: 1.011, 1.073]; p = 0.008) were more likely to be female (AOR 2.068 [95% CI: 1.098, 3.896]; p = 0.024), and use methotrexate (AOR 1.918 [95% CI: 1.249, 2.946]; p = 0.003) as opposed to celecoxib (AOR 0.509 [95% CI: 0.307, 0.844]; p = 0.009) and biologic monotherapy (AOR 0.443 [95% CI: 0.224, 0.876]; p = 0.019). Other factors related to CAM were meloxicam use (AOR 2.342 [95% CI: 1.341, 4.089]; p = 0.003) and traditional therapy (AOR 2.989 [95% CI: 1.647, 5.425]; p = 0.000). The remaining factors were not significant. Conclusion: CAM use is prevalent in patients with RA. Understanding patients and disease related factors associated with higher use of CAM is warranted to improve RA management and provide more rational use of these remedies.